2017
DOI: 10.1371/journal.pbio.2000812
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent temporal channels for auditory processing: Oscillatory neural entrainment reveals segregation of function at different scales

Abstract: Natural sounds convey perceptually relevant information over multiple timescales, and the necessary extraction of multi-timescale information requires the auditory system to work over distinct ranges. The simplest hypothesis suggests that temporal modulations are encoded in an equivalent manner within a reasonable intermediate range. We show that the human auditory system selectively and preferentially tracks acoustic dynamics concurrently at 2 timescales corresponding to the neurophysiological theta band (4–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
78
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 119 publications
18
78
1
Order By: Relevance
“…At the neuronal level, temporal segmentation is argued to be realized through phasealignment of low-frequency (< 8 Hz; delta-theta) neuronal oscillations in auditory cortex to the slow (quasi-rhythmic) fluctuations of the speech signal at the syllabic scale ('speech tracking') (7)(8)(9)(10)(11)(12). This speech tracking possibly indicates the alignment of oscillatory excitability cycles of neuronal ensembles, which can result in perceptual constraints (13) such that speech perception is optimal at syllabic rates that fall within the range of intrinsic auditory cortex oscillations in the delta-theta range (2,14, 15 see also 16).…”
Section: Introductionmentioning
confidence: 99%
“…At the neuronal level, temporal segmentation is argued to be realized through phasealignment of low-frequency (< 8 Hz; delta-theta) neuronal oscillations in auditory cortex to the slow (quasi-rhythmic) fluctuations of the speech signal at the syllabic scale ('speech tracking') (7)(8)(9)(10)(11)(12). This speech tracking possibly indicates the alignment of oscillatory excitability cycles of neuronal ensembles, which can result in perceptual constraints (13) such that speech perception is optimal at syllabic rates that fall within the range of intrinsic auditory cortex oscillations in the delta-theta range (2,14, 15 see also 16).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used various stimuli, such as 21 speech, music, and amplitude-or frequency-modulated sounds, and found robust neural 22 entrainment in auditory cortical areas below 10 Hz, suggesting a high temporal coding 23 capacity in the low frequency range (Luo and Poeppel, 2007 Gross et al, 2013). Previous experiments examined neural entrainment at the 32 low and high frequency ranges and demonstrated that both the neural theta and gamma 33 bands, but not the alpha band, robustly encode acoustic information (Luo and Poeppel,34 2012; Teng et al, 2017). However, two key mechanistic questions remain unresolved: 35 how are acoustic dynamics between the theta and gamma ranges encoded?…”
mentioning
confidence: 99%
“…How does the human auditory system 3 encode acoustic information over wide-ranging timescales to achieve sound recognition? 4Previous work (Teng et al, 2017) demonstrated a temporal coding preference in the 5 auditory system for the theta (4 -7 Hz) and gamma (30 -45 Hz) ranges, but it remains 6 unclear how acoustic dynamics between these two ranges is encoded. Here we generated 7 artificial sounds with temporal structures over timescales from ~200 ms to ~30 ms and 8 investigated temporal coding on different timescales in the human auditory cortex.…”
mentioning
confidence: 99%
See 2 more Smart Citations